A chemical investigation of the essential oil of Eugenia caryophyllus (Sprengel) Bullock et Harrison (Family Myrtaceae) - Egbuji, John Obiora; Bernal-Santos, Rizalina M.; Castillo, Amorita V. (Quezon City Department of Pharmacy, College of Pharmacy, University of the Philippines Diliman, 1977)
The dried flower buds of Eugenia caryophyllus (Sprengel) Bullock et Harrison (formely Eugenia caryophyllata Thunberg) (Family Myrtaceae), were extracted by steam distillation, using the Clevenger apparatus for oils heavier than water. An almost colorless oil was obtained. The yield of the essential oil was 13.6%.
The result of the physicochemical properties were as follows: specific gravity = 1.0575; refractive index = 1.5317; optical rotation = -0.248; blank determination of optical rotation = 3.052; therefore levorotatory; calculated specific rotation = 0.2345; percentage of eugenol as per the oil = 91%. These results were compared with those reported in the literature.
The oil and each fraction were studied for their constituents by using thin layer chromatography, and column chromatography. The main constituent is eugenol.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Diliman, March 1977.
Keywords: Essences and essential oils; Clove tree